A Halotolerant Bacterium Bacillus licheniformis HSW-16 Augments Induced Systemic Tolerance to Salt Stress in Wheat Plant (Triticum aestivum) - Singh, Rajnish P.; Jha, Prabhat N. (Frontiers in Plant Science, 2016)
Certain plant growth promoting bacteria can protect associated plants from harmful effects of salinity. We report the isolation and characterization of 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase bacterium Bacillus licheniformis HSW-16 capable of ameliorating salt (NaCl) stress in wheat plants. The bacterium was isolated from water of Sambhar salt lake, Rajasthan, India. The presence of ACC deaminase activity was confirmed by enzyme assay and analysis of AcdS gene, a structural gene for ACC deaminase. Inoculation of B. licheniformis HSW-16 protected wheat plants from growth inhibition caused by NaCl and increased plant growth (6-38%) in terms of root length, shoot length, fresh weight, and dry weight. Ionic analysis of plant samples showed that the bacterial inoculation decreased accumulation of Na+ content (51%), and increased K+ (68%), and Ca2+ content (32%) in plants at different concentration of NaCl. It suggested that bacterial inoculation protected plants from the effect of NaCl by decreasing level of Na+ in plants. Production of exopolysaccharide by the B. licheniformis HSW-16 can also protect from Na+ by binding this ion. Moreover, application of test isolate resulted in an increase in certain osmolytes such as total soluble sugar, total protein content and a decrease in malondialdehyde content, illustrating their role in the protection of plants. The ability of B. licheniformis HSW-16 to colonize plant root surface was examined by staining the bacterium with acridine orange followed by fluorescence microscopy and polymerase chain reaction (PCR)-based DNA fingerprinting analysis. These results suggested that B. licheniformis HSW-16 could be used as a bioinoculant to improve the productivity of plants growing under salt stress.